THE EFFECT OF BRAIN INFLUENCE TO LEVEL DEMENSION IN POSYANDU LANSIA VILLAGES MRISEN DISTRICT JUWIRING KLATEN - KLATEN, STIKES DUTAGAMA (STIKES DUTAGAMA KLATEN, 2018)
Background: In the elderly, there is a decrease of the brain ability and senility. The decline of memory that happened in the elderly can be fixed by doing brain gymnastics. To handling of dementia can be given by simulation to increase the ability of the right hemisphere that need to give an exercise or game which are need the concentration, orientation, attention to memory and visual. Brain gymnastics is the one of simulations of preventive way to optimize stimulate of brain function to getting better. Goal: Knowing the influence of brain gymnastics toward the level of dementia in the elderly posyandu at Mrisen village, Juwiring, Klaten. Research Methodology: This research used of pre-experimental design research with one group pre-test post-test design. The population in this research is all of the member of elderly posyandu at Mrisen, Juwiring, Klaten. The technique of taking the sample using purposive sampling with 25 respondents. The instrument of this research is using questionnaire of Mini Mental State Examination (MMSE). Result: The result of one group that given treatment by using paired samples T-test showed that there was significance score about 0,000 (p=0,000<0,05%). T count 10,324, T table 2,060. Conclusion: There was the influence of brain gymnastics toward the level of dementia in the elderly posyandu at Mrisen village, Juwiring, Klaten. This is evidenced by the existence of the difference score in pre-test and post-test of MMSE which indicates a decrease in the level of dementia before and after giving treatment of brain gymnastics.